2011
DOI: 10.1111/j.1742-9544.2010.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Referrers' Perceived Utility and Outcomes of Clinical Neuropsychological Assessment in an Adolescent and Young Adult Public Mental Health Service

Abstract: Despite frequent informal or anecdotal acknowledgement of the usefulness of neuropsychological services within various settings, including mental health settings, few studies have formally investigated the satisfaction, perceived utility, or outcomes associated with such a service. This survey-based study evaluated referring clinicians' (n = 35) perceptions of the usefulness and outcomes associated with the provision of clinical neuropsychological assessment and feedback within an adolescent and young adult pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
(35 reference statements)
9
15
0
Order By: Relevance
“…Neuropsychologists are particularly well-positioned to accurately diagnose, treat, and refer individuals with neuropsychiatric symptoms, thereby improving efficiency of healthcare delivery (Allott et al, 2011;Vanderploeg, 1998). While theoretically sound and clinically intuitive, there is very little data supporting this assertion.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Neuropsychologists are particularly well-positioned to accurately diagnose, treat, and refer individuals with neuropsychiatric symptoms, thereby improving efficiency of healthcare delivery (Allott et al, 2011;Vanderploeg, 1998). While theoretically sound and clinically intuitive, there is very little data supporting this assertion.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, another survey of providers' perceptions of neuropsychological services found that referrers reported clinically meaningful outcomes associated with neuropsychological assessments (Allott et al, 2011). As such, neuropsychological services are routinely sought out by providers in medical settings because of the perceived value of their unique contribution to patient care (Johnstone, Coppel, & Townes, 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, assessing for cognitive difficulties in young people with mental health conditions and using this to inform management strategies and assist with school/tertiary liaison and employment options, is of high importance. Clinical neuropsychological assessment has been shown to lead to enhanced diagnostic clarification and more personalised and appropriate treatment/service use in young people with mental illness (Allott, Brewer, McGorry, & Proffitt, 2011). This involves the assessment of cognition (e.g., intelligence, attention, learning, memory, language, problem solving, and academic skills), emotion and behaviour through clinical interview, observation, and the administration of objective neuropsychological tests (Lezak, Howieson, Bigler, & Tranel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is an expanding area of research interest, with pharmacological (Green 2007) and cognitivebased interventions likely to flourish over the next decade. First-episode psychosis services should resource clinical neuropsychologists to provide such specialist input (Allott 2011).…”
Section: Intellectual Disabilitymentioning
confidence: 99%